Pengaruh Komunikasi Menggunakan WhatsApp terhadap Kekompakan Anggota Koperasi Citra Kinaraya di Jawa Tengah - Widyastuti, Khoiriyatun; Gayatri, Siwi; Mariyono, Joko (Jurnal Pekommas, 2024)
Information and communication technology is advancing rapidly. As technology advances, social media also grows and develops. WhatsApp is one of the most widely used social media. This study aims to analyse the factors that influence the use of WhatsApp social media as a communication medium on the cohesiveness of Citra Kinaraya Cooperative members. The research was conducted in December - January, which took place at the Citra Kinaraya Cooperative, Mlatiharjo, Demak. The research method used was a survey with a quantitative approach. The number of respondents was 95 cooperative members—data collection methods by interview, observation, and literature review. The data analysis used in this study used multiple linear regression analysis. This study shows that members of the Citra Kinaraya cooperative have characteristics: aged 41-60 years, the majority are male, have a high school education level, and the length of membership in the cooperative is 1-4 years. The results showed that frequency, duration, attention, age, and education level simultaneously influenced group cohesiveness. On the use of WhatsApp, as seen from frequency, attention duration, age, and education level, only attention partially affects group cohesiveness